Development of Physics E-Modules Based on Inquiry Learning Assisted by Sigil Software to Improve Critical Thinking Skills of High School Students - Freccelia, Erzalina; Putri, Desy Hanisa; Koto, Irwan (Kasuari: Physics Education Journal (KPEJ), 2024)
This study aims to develop an e-module that can be used, improve students' critical thinking skills in the topic of momentum and impulse, and evaluate students' responses to the e-module developed for the learning process. This study uses the Research and Development (R&D) method with the ADDIE model. The findings of the study indicate that: (1) The physics e-module based on inquiry learning, supported by Sigil software, is considered very feasible to use, (2) Students' critical thinking skills increase in the moderate category according to the N-gain test, and (3) Students' responses are considered very good. In conclusion, the physics e-module, based on inquiry learning and assisted by Sigil software, is very suitable for use in physics education and has succeeded in improving students' critical thinking skills on the topic of momentum and impulse. (3) A very good assessment was given to students' responses. In conclusion, the physics e-module assisted by Sigil software, which is based on inquiry learning, is suitable for use in physics teaching and effectively develops students' critical thinking skills on the subject of momentum and impulse.